CSR Decision Making in the UK Food Retail Industry: Explaining Homogeneous and Heterogeneous CSR Behaviour Around the Issue of Food Waste - Neubauer, Luisa (2017)
Corporate Social Responsibility (CSR) has become increasingly important for companies during the past decades. However, in every organization, there are various decisions that have to be made with regard to CSR which determine the observable CSR behaviour of each company. The purpose of this dissertation is to explain how CSR decisions are made on different levels and how this affects homogeneous and heterogeneous CSR behaviour among companies who act in the same market environment. To do this, the context of the food retail industry in the United Kingdom (UK) has been chosen and is explored using the example of food waste. This research draws on the concept of decision making and applies it into the field of CSR in order to define three levels of CSR decision making: CSR engagement, CSR issues and CSR strategy. For the evaluation of CSR strategies, the concept of Sustainable Value Creation was adopted. Because of its explanatory power for organizational behaviour, Institutional Theory (IT) is used as the underlying theoretical lens through which the CSR decisions are analysed. The analysis of websites and expert interviews of four large UK food retailers revealed that the institutional context played a major role in motivating the companies to address food waste as a CSR topic, but was not as prominent in driving the decisions about the specific food waste reduction strategies and activities. The predominant institutional influences differed between those levels as well. Three major explanatory models for homogeneous CSR behaviour between the retailers on the issue level and heterogeneous CSR behaviour on the strategy level have been identified: • The greater the standardization of the area of interest, the more homogeneous the CSR strategies become. • The longer the issue has been on the CSR agenda of all companies, the more homogeneous the CSR strategies become. • The power of the institutional context decreases from the first to the last level of CSR decision making and simultaneously, the homogeneity decreases. While those conclusions are untested and cannot be generalized, by generating those explanations this dissertation provides valuable insights into IT and the food retail industry of the UK and points out an interesting direction for future research.